2009
DOI: 10.1021/cg801193r
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of a Chiral Nanoporous Bimetallic Cyano-Bridged Framework Triggered by Dehydration/Rehydration

Abstract: ABSTRACT:The syntheses, crystal structures, and adsorption/desorption properties of two novel chiral three-dimensional cyanobridged bimetallic assemblies, { [Cu(1R,2Rchxn) (11) , and Z ) 1. Compounds 1 and 2 can be described as nanoporous cyano-bridged frameworks, in which alternating trans- 6 diamondoid frameworks. In both structures there are large cavities filled with H 2 O molecules which show guestdependent dynamic behavior. The chemical rearrangement of the framework is driven by the loss or additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 78 publications
0
9
0
Order By: Relevance
“…An alternative way to induce a well-defined configuration about a metal cation relies on the use of organic ligands and transfer of the chiral information to the metal center. 18,19 The same enantiopure diamine has been employed in the crystallization-induced resolution of biaryl derivatives. We have focused on the combination of Δ/Λ metal chirality in trisIJchelating) pseudooctahedral complexes and RR configuration in the chelating ligand R,R-1,2-diaminocyclohexane (R, R-chxn).…”
Section: Introductionmentioning
confidence: 99%
“…An alternative way to induce a well-defined configuration about a metal cation relies on the use of organic ligands and transfer of the chiral information to the metal center. 18,19 The same enantiopure diamine has been employed in the crystallization-induced resolution of biaryl derivatives. We have focused on the combination of Δ/Λ metal chirality in trisIJchelating) pseudooctahedral complexes and RR configuration in the chelating ligand R,R-1,2-diaminocyclohexane (R, R-chxn).…”
Section: Introductionmentioning
confidence: 99%
“…However, specific reasons for lattice strain could not be found as specific interatomic distances (probably void space may be concerned). Contrary to heating behavior [11][12][13], releasing crystalline water accompanying by drastic structural change is not responsible for this cooling behavior. Additionally, we could not add hydrogen atoms of crystalline water molecules and we could not discuss detailed features of hydrogen bonds.…”
Section: Resultsmentioning
confidence: 59%
“…Furthermore, 1 and several related coordination polymers exhibited reversible releasing and containing of guest crystalline water molecules by heating and cooling. The crystal structure *Address correspondence to this author at the Department of Chemistry, Faculty of Science, Tokyo University of Science, 1-3 Kagurazaka, Shinjukuku, Tokyo 162-8601, Japan; Tel: +81-3-5228-8271; Fax; +81-3-5261-4631; E-mail: akitsu@rs.kagu.tus.ac.jp determination based on powder XRD data reported by Sereda et al [11][12][13] suggested that the resulting reversible structural changes were between zigzag (containing water molecules) and straight (losing water molecules) onedimensional cyanide-bridges of host MOF. Herein, we have investigated thermally accessible structural changes of 1 by cooling less than room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, extremely long semi-coordination bonds of Cu(II) complexes [18][19][20][21][22] sometimes have potential advantage to form flexible crystals against external temperature changes, which is anisotropic along the Jahn-Teller axis [23][24][25]. However, the present systems show anisotropically negative thermal expansion caused by not coordination bonds around lanthanide nor iron atoms but intermolecular hydrogen bonds with isotope effect for the first time.…”
Section: Resultsmentioning
confidence: 94%